The Mediating Role of Computational Identity in the Relationship between Computational Thinking Skills and Academic Self-Efficacy - Belay Sitotaw Goshu; Muhammad Ridwan (Budapest International Research and Critics University, 2025)
Computational thinking (CT) has emerged as a critical 21st-century skill, yet its motivational and psychological correlates in higher education remain underexplored, particularly in African contexts. Creative interest (CI) and academic self-efficacy (ASE) represent key motivational mechanisms that may link CT perceptions to broader academic confidence. Purpose: This study examined the direct and indirect relationships among computational thinking, creative interest, and academic self-efficacy among undergraduate students, testing whether creative interest mediates the effect of CT on ASE. Methods: A cross-sectional survey was administered to 357 undergraduate students at Dire Dawa University, Ethiopia. Validated self-report scales measured overall and subscale levels of CT, CI, and ASE. Data were analyzed using descriptive statistics, Pearson correlations, confirmatory factor analysis (CFA), and bootstrapped mediation analysis with PROCESS macro. CFA supported the distinctiveness of the three constructs with acceptable fit (CFI = 0.92, RMSEA = 0.072) and strong validity (AVE > 0.76). CT showed strong positive correlations with CI (r = 0.594) and ASE (r = 0.632). Mediation analysis revealed a significant total effect of CT on ASE (β = 0.356, p < .001), a significant direct effect after mediation (β = 0.289, p < .001), and a small but significant indirect effect via CI (β = 0.067, 95% bootstrap CI [0.033, 0.101]), accounting for 18.8% of the total effect. The model explained 42.5% of variance in ASE. Conclusion: Computational thinking perceptions enhance academic self-efficacy both directly and partially through creative interest, highlighting a motivational pathway in which CT fosters creative identity that, in turn, supports efficacy beliefs. Ethiopian universities should integrate CT training with activities that explicitly link computational skills to creative expression and self-regulated learning to maximize motivational and efficacy benefits.